2014
DOI: 10.3941/jrcr.v8i10.1804
|View full text |Cite
|
Sign up to set email alerts
|

Pericardioesophageal Fistula Following Left Atrial Ablation Procedure

Abstract: We present a case of pericardioesophageal fistula formation in a 40 year old male who 23 days after undergoing a repeat ablation procedure for atrial fibrillation developed chest pressure, chills and diaphoresis.  After initial labs and tests that demonstrated no evidence for acute myocardial ischemia, the patient underwent CT angiography of the chest.  The study revealed pneumopericardium and a pericardial effusion.  Suspicion was raised of perforation of the posterior left atrial myocardial wall with injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Previous case studies reported that pericardial-esophageal fistula was successfully treated with supportive care or endoscopic intervention. 6) 7) 8) 9) In this case, pericardial-esophageal fistula was successfully healed by very strict fasting over 2 weeks with fluid and antibiotic therapy after drainage of inflammatory body fluids. Although a proton pump inhibitor was empirically administered after ablation due to the possibility of esophageal injury, esophageal perforation eventually developed.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Previous case studies reported that pericardial-esophageal fistula was successfully treated with supportive care or endoscopic intervention. 6) 7) 8) 9) In this case, pericardial-esophageal fistula was successfully healed by very strict fasting over 2 weeks with fluid and antibiotic therapy after drainage of inflammatory body fluids. Although a proton pump inhibitor was empirically administered after ablation due to the possibility of esophageal injury, esophageal perforation eventually developed.…”
Section: Discussionmentioning
confidence: 80%
“…Clinical detection of a pericardial-esophageal fistula can be difficult because conspicuous signs, such as systemic embolization and gastrointestinal tract bleeding, are not present. 6) 7) 8) 9) Therefore, to recognize the condition and avoid delay of an appropriate diagnosis, clinical suspicion should increase if there are any chest symptoms or signs suggestive of extensive tissue injury. In this case, after AF ablation, the patient complained of persistent retrosternal pain for more than 9 days, which is suggestive of extensive tissue injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is imperative that physicians recognize the signs and symptoms of atrio-esophageal fistula. Time from ablation to symptom onset has been reported to be from 2 days to 5 weeks, with the most common occurrence at 10 to 17 days [ 4 , 11 , 23 , 24 ] Most patients present with the constellation of fever and neurologic deficits, often secondary to air emboli [ 24 26 ]. Less commonly, there is septicemia with oral flora bacteremia, chest pain, and hematemesis/melena [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…When reviewing the literature regarding esophago-mediastinal fistulous formation, we found 23 cases of esophageal perforation without a fistulous communication with the left atrium. 6,7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Only one of the 23 cases was screened early after ablation having a normal esophagoscopy, before developing perforation two weeks later 4 (Table 1). Park et al 4 also reported that another patient, who likely died of esophageal-atrial fistula, had a normal endoscopy on the second day after the procedure.…”
Section: Esophagus Perforation and Fistula Developmentmentioning
confidence: 99%